Response of varying weight groups of finishing pigs to antibiotic supplementation - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1983)
Two feeding trials involving a total of 320 head of finishing pigs were used to evaluate the effect of feeding an antibiotic to three groups selected from within a farrowing group. Pigs were divided by weight into group A (heaviest 50%), group B (25-50%) and group C (lightest 25%). Each group was assigned treatments of either 4 weeks of 100 gm of tylan-sulfa followed by 4 weeks of 40 gm/ton of tylan or no antibiotic for the 8-week trial. All groups responded to antibiotic feeding the initial 4 weeks with improved growth rate. The second 4 weeks resulted in a mixed response in that some groups not receiving antibiotic showed a compensatory gain. No group treatment interaction was observed. Eight-week performance of all groups would not indicate any advantage to feeding antibiotic to the finishing pig, regardless of weight.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Finishing pigs; Antibiotic supplementation